Climate, disease and society in late-medieval Ireland - Ludlow, Francis (My University, 2020)
Palaeoclimatic data are used to track the significant changes in atmospheric circulation patterns and weather conditions that affected Ireland between 1000 and 1500CE. How these climatic developments and associated shifts in the epidemiological environment were mapped onto Irish society is explored using a tree-ring chronology reflecting the retreat and advance of oak woodland. Years characterised by significant weather-related food scarcities are identified from the Irish Annals in combination with the independent record of English chronicles, grain yields and prices. Between the thirteenth and the fifteenth centuries the experience of the two countries is shown to have diverged. It is suggested that in late-medieval Ireland scarcity heightened the resort to violence and was from 1348 often a proximate cause of plague outbreaks. In combination, scarcity, violence and plague helped entrap fifteenth-century society in a low-level equilibrium of sparse population, economic under-development, scarcely disguised poverty and low resilience to natural hazards.
PUBLISHED
Keywords: Digital Humanities; Making Ireland; Smart & Sustainable Planet; Antarctic ice core; British History; CLIMATE; CLIMATE CHANGE; CLIMATE-CHANGE; Changing Climate; Climate Change; Climate Change; Climate Change; Climate Change; Climate Change Impacts on the Environment; Climate History; Climate-Conflict Linkages; Conflict and Dispute Resolution; ECONOMIC HISTORY; Economic History; Economic History; Economic History; GLOBAL CLIMATE-CHANGE; GREENLAND ICE CORE; HOLOCENE CLIMATE; Historical Climate Research; Historical Climatology; Historical GIS; Historical Geography; Historical geography of Ireland; ICE CORE; ICE-CORE; Ice cores; Irish economic history; Irish History; Irish climate; PALAEOCLIMATE; PALEOCLIMATE; Political, Social, Economic History; Poverty and the Poor; TREE RINGS; Volcanic Eruptions; bubonic plague; climate change impacts; climate research; dendrochronology; disease history; economic history; environmental history; explosive volcanism; Health; History